GAGASAN PEMBADANAN PENGUJIAN PREVENTIF KE DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA (PERBANDINGAN DENGAN CONSEIL CONSTITUTIONNEL DE LA RÉPUBLIQUE FRANÇAISE) - Sukmawati, Irma Oktavia; Isharyanto, Isharyanto (Res Publica: Jurnal Hukum Kebijakan Publik, 2018)
This research aims to analyze how the implementation of judicial preview in the French Constitutional Council. Furthermore,, the author also examine what matters that implicate the acceptance of the idea of judicial preview when implanted into the constitutional system of the Republic of Indonesiaby examine and develop a mechanism to check list or a system applied in French Constitutional Council named judicial preview. To ensure that it each law making process in accordance with the constitution so that decreasing the number of judicial review in the Constitutional Court In this research, a method use normative juridical by using statute approach, and comparative approach. From the research explores a judicial preview mechanism in Constitutional Court to verify the value of constitutionality a draft law, so that the embodying of judicial preview mechanism in the constitutional system of the Republic of Indonesia is embodied as an authority and additional mechanism for Indonesian Constitutional Court.